Enantioselective remote functionalisation of cyclic amines by engineered P450BM3 variants - Zhang, Y (2022)
P450 enzymes activate C–H bonds via the insertion of an oxygen atom from atmospheric dioxygen under ambient conditions in water and accept a broad array of endogenous and exogenous organic substrates. P450BM3 (CYP102A1) has a unique structure, with the electron-transfer reductase domain fused to the haem monooxygenase domain. This makes P450BM3 catalytically self-sufficient and promotes high turnover rates. Functionalised cyclic amines are versatile intermediates in drug synthesis and important fragment molecules in drug discovery. Selective oxidation of unactivated ring aliphatic C–H bonds is an attractive route to cyclic amine derivatives; however, classical synthetic methods are limited in scope and lack enantioselectivity. The application of engineered P450 enzymes for selective functionalisation of cyclic amines is surprisingly under-explored.